KARAKTERISTIK AERODINAMIKA PESAWAT AMFIBI DENGAN METODE COMPUTATIONAL FLUID DYNAMICS (CFD) - Saputra, Meri Andani; Supardi, Nurul Iman; Suandi, Agus (UNIB Press, 2023)
Aerodynamics is the study of the flow field and the forces caused by relative motion between the aircraft (aircraft body or other parts) and the surrounding air. The study of aerodynamics involves calculating the speed, temperature and pressure that occur due to the relative motion of an object in the air. The pressure and frictional forces acting at every point on the surface of an object cause lift, drag, and side forces. One way to calculate the aerodynamic characteristics of the aircraft is by using the CFD method. Computational fluid dynamics or CFD is the analysis of systems involving fluid flow, heat transfer and related phenomena such as chemical reactions by means of computer-based simulations. The goal to be achieved is to determine the correlation of the lift coefficient and drag coefficient of the seaplane, it is necessary to carry out a CFD simulation. The research methodology was carried out using Computational Fluid Dynamics (CFD) simulations at speeds of 20 m/s, 40 m/s and 60 m/s and Angle of Attack 0°, 5°, 10°, 15°, 20°, 25° dan 30°. The simulation results show that the lowest value is at AoA 0^° and the highest is at AoA 30°. for each speed, but at a speed of 20 m/s the highest value is at AoA 25°because at AoA 30° the value decreases causing a stall . value increases with each variation of speed and angle of attack.